Experimental Simulation Investigation on Mechanism and Criterion of Impact‐Induced Rockburst in Gaoloushan Deep Tunnel - Chao Ren; Xiaoming Sun; Manchao He; DongQiao liu; JinKun Yang; Kunbo Zhang (Energy Science & Engineering)
ABSTRACT During the excavation of a deep‐buried tunnel by the drilling and blasting method, the dynamic stress of blasting may cause the disorderly release of high energy in the rock mass during the blasting process of deep high‐energy rock. Blasting vibration is one of the main factors inducing dynamic disasters (such as rockbursts) in the surrounding rock. An impact‐induced rockburst occurred in the Gaoloushan deep‐buried tunnel. In this paper, the simulation experiment of this type of rockburst was carried out by using the impact rockburst experimental system. The two rockbursts that occurred during the experiment formed “V” type pits, which were consistent with the on‐site rockburst situation; therefore, it proved the rationality of this experiment. The results showed that the total displacement characteristics of impact‐induced rockbursts had obvious suddenness, and the intensity of impact‐induced rockbursts showed characteristics from weak to strong. In addition, it was also found that the rupture parameters of the rock mass in rockbursts showed a compound exponential growth relationship with time. As a typical mode of instantaneous rockburst failure, the mechanism of impact‐induced rockburst could be regarded as the result of the combined action of shear crack and tension‐shear crack, which played a dominant role, reflecting the characteristics of sudden fracture development. The generation of impact‐induced rockbursts occurred when the peak value of static load and disturbance stress wave reached a certain value. On this basis, the rockburst criterion was proposed.